Synthesis of Spirocyclopropane Scaffolds: A Review - Patel, Chirag D.; Damiri, Fouad; Parmar, Mehul P.; Vala, Disha P.; Berrada, Mohammed; Patel, Hitendra M. (Synthesis, 2025)
This review highlights different synthetic strategies for preparing a spirocyclopropane moiety, covering the literature from 1989 to 2024. The spirocyclopropane moiety is a structural scaffold that is used to access synthetic libraries of highly functionalized spirocarbo- and heterocyclic molecules. The review showcases different routes for the synthesis of spirocyclopropanes that utilize distinct precursors and methodologies, including cascade reactions, cyclopropanation, Michael-initiated ring closure (MIRC), and one-pot and multicomponent synthesis. These discussions are organized around the oxindole core, which include isatin, oxindole, 3-chlorooxindole, and 3-alkenyl oxindoles. Additionally, this review explores various ylides and other techniques. The goal of this review is to provide a background for synthetic chemistry researchers to develop new ideas and novel synthetic routes to spirocyclopropanes. 1 Introduction2 Synthesis of Spirocyclopropanes from 3-Chlorooxindole Derivatives3 Synthesis of Spirocyclopropanes from Isatin Derivatives3.1 Synthesis of Spirocyclopropanes from Alkylidene Oxindole Derivatives3.2 Synthesis of Spirocyclopropanes from Diazooxindole Compounds4 Synthesis of Spirocyclopropanes from 1,3-Diones5 Synthesis of Spirocyclopropanes from N-Ylides6 Synthesis of Spirocyclopropanes from S-Ylides7 Miscellaneous Syntheses of Spirocyclopropanes8 Conclusion9 List of Abbreviations
Keywords: spirocyclopropanes; cyclopropanation; spirooxindoles